2015
DOI: 10.1002/jctb.4660
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biodegradation of aged petroleum hydrocarbons in soils by glucose addition in microbial fuel cells

Abstract: BACKGROUND Bioelectrochemical remediation of soils contaminated by petroleum hydrocarbons has received increasing attention as an effective approach to remove pollution with simultaneous electricity generation. RESULTS Here, glucose was added as a co‐substrate in this system. The charge output of soil microbial fuel cells (MFCs) was enhanced by 262%, and the total petroleum hydrocarbon degradation rate increased by 200%. According to the increased dehydrogenase and polyphenol oxidase activities, the exogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 26 publications
2
41
0
2
Order By: Relevance
“…It was noted that the band 35 (Alcanivorax, a strain of typical hydrocarbon degradation bacteria (Cui et al, 2008)) was distinctly stimulated in Layer 4 of LS and HS, indicating that the improved mass transport by sand promoted the population of hydrocarbon degradation bacteria (Li et al, 2015). The H and S of LS and HS were lower than those of CK, showing a selective enrichment of functional communities (Li et al, 2014b; Lu et al, 2014b).…”
Section: Discussionmentioning
confidence: 95%
“…It was noted that the band 35 (Alcanivorax, a strain of typical hydrocarbon degradation bacteria (Cui et al, 2008)) was distinctly stimulated in Layer 4 of LS and HS, indicating that the improved mass transport by sand promoted the population of hydrocarbon degradation bacteria (Li et al, 2015). The H and S of LS and HS were lower than those of CK, showing a selective enrichment of functional communities (Li et al, 2014b; Lu et al, 2014b).…”
Section: Discussionmentioning
confidence: 95%
“…Dehydrogenase is responsible for the biological oxidation of organic compounds, and its activity can assess the protons catalysed by intermediate products . Some studies indicated that electric field and iron ions were able to enhance dehydrogenase activity . Additionally, previous research showed that electrocoagulation has the capability to increase the relative abundances of nitrogen removal microorganisms to improve the nitrogen removal performance .…”
Section: Resultsmentioning
confidence: 99%
“…A charge output of 918 C was transferred, and 37 mW m −2 (366 mV, 102 mA m −2 , across 1000 Ω resistor) of the maximum power density was achieved, which was consistent with that previously reported (39 mW m −2 ; Table ). With the help of sand amendment and glucose addition, the performance of multianode soil MFCs was further promoted ,. Additionally, Zhang et al.…”
Section: Organic‐contaminant Degradationmentioning
confidence: 99%
“…Moreover, it should be noted that the power production of soil MFCs (≈80 mA m −2 , 1000 Ω) was around 10‐fold lower than those of liquid medium MFCs (≈800 mA m −2 , 1000 Ω); this suggests that a fixed‐area cathode can afford a much larger area anode in soil than that in water applications . In view of the abovementioned advantages, a multianode air‐cathode soil MFC with one cathode was designed to extend the anode in soil contaminated with aged petroleum hydrocarbons (Figure d) ,,. More than three anode layers in this type of soil MFC could be explored to test the possibility of long‐range bioremediation with much regard for practicality and cost.…”
Section: Key Issues Of Soil Mfc Remediationmentioning
confidence: 99%
See 1 more Smart Citation